Prevalence and Antimicrobial Resistance of Bacteria Isolated from Clinical Specimens of COVID-19 Patients Admitted to Fatemeh Zahra Hospital in Sari, Iran - Azizi , Soheil; Forouzanfar, Amirreza; Taheri, Marzieh; Abdi Seyedmahalleh, Fateme; Dadfar, Alireza; Basirpour, Bahareh; Yasbolaghi Sharahi, Javad; Hassanzadeh, Faezeh; Mirzakhani, Maryam; Mahdlou, Aylar; Karimi-Yazdi, Mohammadmahdi (Novelty in Biomedicine, 2026)
Background: The COVID-19 pandemic has heightened concerns over secondary bacterial infections, which worsen outcomes in hospitalized patients. This study investigated the prevalence and antibiotic resistance of bacteria isolated from clinical specimens of COVID-19 patients admitted to Fatemeh Zahra Hospital in Sari, Iran. Materials and Methods: From September 2020 to August 2022, 3314 COVID-19 patients were included, with 55 positive cultures (including bacterial and fungal) obtained from 47 patients. The most common sources were urine (52.7%) and respiratory samples (38.1%). Gram-negative bacteria (58.9%), primarily Enterobacteriaceae (84.8%), were predominant, followed by Pseudomonas spp. and Acinetobacter. Gram-positive isolates included Staphylococcus aureus and coagulase-negative staphylococci. ICU-admitted patients showed higher co-infection rates, with increased mortality linked to bacterial infections. Antimicrobial susceptibility testing revealed concerning resistance patterns, including high resistance to ceftazidime (85% in Gram-negatives), imipenem (45% in Acinetobacter), and amikacin (50% in Pseudomonas), underscoring the challenge posed by multidrug-resistant organisms (MDROs). Among Gram-negative isolates, 30% were extensively drug-resistant (XDR). Results: Despite a low overall co-infection rate (1.3%), bacterial infections significantly impacted disease severity and mortality. The findings align with regional studies highlighting Gram-negative pathogens as major contributors. Compared with pre-pandemic reports from Iran, resistance rates to carbapenems increased from ~43% to 65% among Acinetobacter baumannii. The rise in antimicrobial resistance (AMR) underscores the need for strict antibiotic stewardship and robust infection control measures. Conclusion: This study emphasizes the critical role of bacterial co-infections in COVID-19 outcomes and calls for continuous surveillance to guide effective treatment strategies during the pandemic.